The flexible loop of Staphylococcus aureus IsdG is required for its degradation in the absence of heme - Reniere, Michelle L. (2011)
Degradation of specific native proteins allows bacteria to rapidly adapt to changing environments when the activity of those proteins is no longer required. Although these processes are vital to bacterial survival, relatively little is known regarding how bacterial proteins are recognized and targeted for degradation. Staphylococcus aureus is an important human pathogen that requires iron for growth and pathogenesis. In the vertebrate host, S. aureus fulfills its iron requirement by obtaining heme-iron from host hemoproteins via IsdG- and IsdI-mediated heme degradation. IsdG and IsdI are structurally and mechanistically analogous but are differentially regulated by iron and heme availability. Specifically, IsdG is targeted for degradation in the absence of heme. Therefore, we utilized the differential regulation of IsdG and IsdI to investigate the mechanism of regulated proteolysis. In contrast to canonical protease recognition sequences, we show that IsdG is targeted for degradation by internally coded sequences. Specifically, a flexible loop near the heme-binding pocket is required for IsdG degradation in the absence of heme.